Chronic pacing and adverse outcomes after transcatheter aortic valve implantation. Issue 20 (10th August 2015) - Dizon, Jose' M; Nazif, Tamim M; Hess, Paul L; Biviano, Angelo; Garan, Hasan; Douglas, Pamela S; Kapadia, Samir; Babaliaros, Vasilis; Herrmann, Howard C; Szeto, Wilson Y; Jilaihawi, Hasan; Fearon, William F; et al.
Abstract : Objective: Many patients undergoing transcatheter aortic valve implantation (TAVI) have a pre-existing, permanent pacemaker (PPM) or receive one as a consequence of the procedure. We hypothesised that chronic pacing may have adverse effects on TAVI outcomes. Methods and results: Four groups of patients undergoing TAVI in the Placement of Aortic Transcatheter Valves (PARTNER) trial and registries were compared: prior PPM (n=586), new PPM (n=173), no PPM (n=1612), and left bundle branch block (LBBB)/no PPM (n=160). At 1 year, prior PPM, new PPM and LBBB/no PPM had higher all-cause mortality than no PPM (27.4%, 26.3%, 27.7% and 20.0%, p<0.05), and prior PPM or new PPM had higher rehospitalisation or mortality/rehospitalisation (p<0.04). By Cox regression analysis, new PPM (HR 1.38, 1.00 to 1.89, p=0.05) and prior PPM (HR 1.31, 1.08 to 1.60, p=0.006) were independently associated with 1-year mortality. Surviving prior PPM, new PPM and LBBB/no PPM patients had lower LVEF at 1 year relative to no PPM (50.5%, 55.4%, 48.9% and 57.6%, p<0.01). Prior PPM had worsened recovery of LVEF after TAVI (Δ=10.0 prior vs 19.7% no PPM for baseline LVEF <35%, p<0.0001; Δ=4.1 prior vs 7.4% no PPM for baseline LVEF 35–50%, p=0.006). Paced ECGs displayed a high prevalence of RV pacing (>88%). Conclusions: In the PARTNER trial, prior PPM, along with new PPM and chronic LBBB patients, had worsened clinical and echocardiographic outcomes relative to no PPM patients, and the presence of a PPM was independently associated with 1-year mortality. Ventricular dyssynchrony due to chronic RV pacing may be mechanistically responsible for these findings. Trial registration number: (ClinicalTrials.gov NCT00530894 ).